JIHAD EKOLOGI MELAWAN EKSPLOITASI TAMBANG EMAS DI BANYUWANGI SEBAGAI PENGUATAN GREEN CONSTITUTION - Syamsul Arifin; Moh. Anas Kholish; In'amul Mushoffa; Abul Ma’ali (Peradaban Journal of Religion and Society, 2023)
This research was conducted to study (1) How is the portrait of the ecological damage caused by the management of a gold mine in Banyuwangi? (2) How is the ecological jihad of the gloved people related to environmentally friendly management of natural resources as strengthening the green constitution in responding to gold mining in Banyuwangi? This study resulted in findings that: First, gold mining in Banyuwangi has caused air and sea/coastal pollution, damaged roads, mud floods, and vulnerability to tsunami-prone areas on the south coast of Banyuwangi. Second, various jihad efforts or actions with religious nuances such as istighasah, praying together, reciting hizb nashar as a form of ecological jihad of people wearing gloves in saving the environment has not succeeded in saving the Mount Tumpang Pitu and Mount Salakan areas from mining exploitation. This condition implies the increasing importance of the green constitutionalization of the structural model by granting the right of nature or treating nature as a legal subject in the norms of the 1945 Constitution of the Republic of Indonesia.   Penelitian ini dilakukan untuk mempelajari (1) Bagaimana potret kerusakan ekologi yang diakibatkan oleh pengelolaan tambang emas di Banyuwangi? (2) Bagaimana jihad ekologis kaum bersarung terkait pengelolaan sumber daya alam yang ramah lingkungan sebagai penguatan green constitution dalam menyikapi penambangan emas di Banyuwangi? Penelitian ini menghasilkan temuan bahwa: Pertama, Penambangan emas di Banyuwangi telah menyebabkan pencemaran udara dan laut/pantai, kerusakan jalan, banjir lumpur, merentankan kawasan rentan tsunami di pesisir selatan wilayah Banyuwangi. Kedua, berbagai upaya jihad atau aksi bernuansa religius seperti istighasah, doa bersama, membaca hizb nashar sebagai bentuk jihad ekologis kaum bersarung dalam penyelamatan lingkungan belum berhasil menyelamatkan kawasan Gunung Tumpang Pitu dan Gunung Salakan dari eksploitasi tambang. Kondisi ini menyiratkan semakin pentingnya konstitusionalisasi hijau model struktural dengan memberikan hak alam (right of nature) atau memperlakukan alam sebagai subjek hukum dalam norma UUD NRI 1945.